The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12185-013-1382-0
|View full text |Cite
|
Sign up to set email alerts
|

The biology of thrombopoietin and thrombopoietin receptor agonists

Abstract: Thrombopoietin (TPO) is the major physiological regulator of platelet production. TPO binds the TPO receptor, activates JAK and STAT pathways, thus stimulating megakaryocyte growth and platelet production. There is no ''sensor'' of the platelet count; rather TPO is produced in the liver at a constant rate and cleared by TPO receptors on platelets. TPO levels are inversely proportional to the rate of platelet production. Early recombinant TPO molecules were potent stimulators of platelet production and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
194
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(212 citation statements)
references
References 106 publications
1
194
0
4
Order By: Relevance
“…45 Altogether, our results showed that one-fourth of primary AIHA patients require at least 2 lines of therapy, about 13% require 3, and a small fraction (4%) require $4 lines; the most severe cases and the mixed and atypical forms had a 3-fold increased risk of relapse or unresponsiveness to therapy. Younger age was also associated with a severe clinical presentation and an increased risk of relapse and refractoriness, probably due to a more aggressive immune reactivity.…”
Section: Discussionmentioning
confidence: 56%
“…45 Altogether, our results showed that one-fourth of primary AIHA patients require at least 2 lines of therapy, about 13% require 3, and a small fraction (4%) require $4 lines; the most severe cases and the mixed and atypical forms had a 3-fold increased risk of relapse or unresponsiveness to therapy. Younger age was also associated with a severe clinical presentation and an increased risk of relapse and refractoriness, probably due to a more aggressive immune reactivity.…”
Section: Discussionmentioning
confidence: 56%
“…9 Among the small, non-peptide c-Mpl agonists, 10,11 eltrombopag has been successfully employed to stimulate platelet production in patients suffering from IT caused by mutations of the MYH9 gene, immune thrombocytopenia (ITP), and thrombocytopenia due to hepatitis C infection. [12][13][14] Moreover, improvement of thrombocytopenia has been obtained in patients with acute myeloid leukemia (AML) and MDS.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombopoietin (TPO) is known to be critical for both HSC maintenance and platelet production [34][35][36][37][38][39][40]. SanjuanPla et al [41] have recently identified, in the mouse, a TPOdependent platelet-biased HSC expressing Sca-1, c-kit, CD150, and von Willebrand factor (vWF), which exists at the apex of the hematopoietic hierarchy and which not only generates platelets over the short and longer term, but also can give rise to both myeloid-and lymphoid-biased HSCs.…”
Section: Introductionmentioning
confidence: 99%